Combined Fluvial and Pluvial Flood Inundation Modelling for a Project Site. (2016) - Patra, Jagadish Prasad; Kumar, Rakesh; Mani, Pankaj
Abstract: There are many sources of flooding viz. river flooding, coastal flooding, surface water flooding, drain and sewer flooding, groundwater flooding etc. This study envisages identification of various flooding sources, estimation of maximum floods and their routing through drainage system for a proposed industrial site. The digital elevation model (DEM) is developed from DGPS points, 0.5 m interval contour and spot levels and contours extracted from survey of India topographical maps for the surrounding area. The L-moments based rainfall frequency analysis has been performed to estimate 1 day maximum rainfall for various return periods. The synthetic unit hydrographs are derived from catchment characteristics and flood hydrographs for 10, 25, 50 and 100 year return periods are computed. The two major source of flooding are: flow in the drain and rainfall induced catchment flooding are modelled using MIKE FLOOD package. The bathymetry of the flood plain around the plant site at 5 m grid size is created from DEM in the 2-D modelling in MIKE-21. Local rainfall over the proposed industrial site is also modelled in the MIKE-21. The spills from drainage network due to upstream catchment flow and local rainfall are simulated in coupled MILE-11 and MIKE-21 i.e., MIKE FLOOD package. Various scenarios of flooding like flow in the drain and with and without rainfall of various return periods are simulated to develop corresponding flood inundation maps. Other parameters like flood extent, depth, level, duration and maximum flow velocity are also computed. The safe grade levels for the industrial site are proposed considering these parameters to safe guard the flood disaster.